Studi Kinerja Teoritis Dan Konsumsi Energi Pengkondisian Udara Menggunakan R22 Dan R290 - Matheus M. Dwinanto; Wenseslaus Bunganaen; Indra H. Syaifullah (Jurusan Teknik Mesin, Fakultas Sains dan Teknik, Universitas Nusa Cendana, 2021)
The use of more environmentally friendly hydrocarbon refrigerants in air conditioning systems has become a demand and a central issue in the future. This article presents the simulation results of the comparison of the use of R22 and R290 on the performance and energy consumption per year of air conditioning systems. The thermodynamic analysis of the system using the two refrigerants used CoolPack software version 1.50 at various evaporation temperatures, with the condensation temperature held constant. The important quantities analyzed are refrigerant mass flow rate, compressor pressure ratio, and refrigerant gas temperature leaving the compressor, heat release in the condenser, compressor power, performance coefficient, and energy consumption. The results of this study indicate that the performance and energy consumption of systems that use the two types of refrigerants basically have no significant difference. However, the R290 has a much lower compressor exit temperature which results in a longer compressor life. In addition, R290 is more environmentally friendly than R22, so the use of R290 is highly recommended.